Simulation analysis to optimize the performance of a homojunction -- In₀.₇Ga₀.₃N solar cell - Hussain, S.; Prodhan, Md. T.; Rahman, Md. M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Simulation analysis has been carried out to determine the perfect structural parameters of a homojunction -- In₀.₇Ga₀.₃N solar cell to obtain maximum overall efficiency. It has been demonstrated that a -layer of 16 nm, an intrinsic layer (-layer) of 0.5-μm, and a -layer of 3-μm thickness with specific doping concentrations of 1·10²⁰ cm⁻³ for -layer and 1·10¹⁸ cm⁻³ for -layer allow us to achieve the maximum efficiency 29.21%. The solar cell structure provides an open circuit voltage of 1.0 V, a short circuit current density of 33.15 mA/cm², and the percentage of fill factor value of 88.03%. However, the efficiency drops drastically if the dislocation density in the -layer is higher than 1·10¹⁴ cm⁻³, and the unintentional doping concentration within the -layer is beyond 1.5·10¹⁶ cm⁻³ of the structure. Для визначення ідеальних структурних параметрів сонячного елемента на основі In₀.₇Ga₀.₃N з -- гомопереходом проведено моделювання, щоб отримати максимальну загальну ефективність. Показано, що параметри – -шар товщиною 16 нм, власний шар (-шар) товщиною 0,5 мкм і -шар товщиною 3 мкм з відповідними концентраціями легування 1·10²⁰ см⁻³ для n-шару і 1·10¹⁸ см⁻³ для p-шару – дозволяють досягти максимальної ефективності 29,21%. Конструкція сонячного елемента забезпечує напругу холостого ходу 1,0 В, густину струму короткого замикання 33,15 мА/см² і коефіцієнт заповнення 88,03%. Однак ефективність різко падає, якщо щільність дислокацій в i-шарі більше ніж 1·10¹⁴ см⁻³, а фонова концентрація домішок в i-шарі перевищує 1,5·10¹⁶ см⁻³.